Drivers and barriers analysis for green manufacturing practices in Malaysian SMEs : A preliminary findings - Raja Ghazilla, R.A.; Sakundarini, N.; Abdul Rashid, S.H.; Ayub, N.S.; Olugu, E.; Musa, S.N. (2014)
Nowadays, manufacturing industries are challenged to address stringent regulation on environmental issues due to the scarcity of natural resources, global warming, and waste disposal problems. This situation inspired more commitment among manufacturers to develop green manufacturing practices. Drivers and harriers to green manufacturing practices in Small Medium Enterprises (SMEs) differ from larger enterprises. In SMEs, specific characteristics are identified, such as: generation of less environmental data, fewer resources, less environmental expeitises and experiences. Environmental performances of SMEs mostly are driven by the intention of company owners, This paper reports preliminary findings of our work that focuses on identifying drivers and barriers that motivate and hindering green manufactunng practices. The Delphi method is used to explore, identify and verify the drivers and barriers of green manufacturing practices by obtaining expert consensus in a series of questionnaires. This study gives insight to industries that need to change their traditional manufacturing practices into green manufacturing practices. This study also can facilitate industries to prioritize key factors that need to be considered when adopting green manufactu,ring practices.